2013
DOI: 10.5194/acp-13-4815-2013
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of summer surface water vapor isotopic composition above the Greenland Ice Sheet

Abstract: We present here surface water vapor isotopic measurements conducted from June to August 2010 at the NEEM (North Greenland Eemian Drilling Project) camp, NW Greenland (77.45 N, 51.05W, 2484ma.s.l.). Measurements were conducted at 9 different heights from 0.1m to 13.5m above the snow surface using two different types of cavity-enhanced near-infrared absorption spectroscopy analyzers. For each instrument specific protocols were developed for calibration and drift corrections. The intercomparison of corrected resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
236
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(259 citation statements)
references
References 49 publications
18
236
5
Order By: Relevance
“…We therefore do not expect the snow surface to take up a significant isotopic signal from the surface hoar formed during the night. We do notice that, during clear-sky days, the diurnal cycle of sublimation/condensation is reflected in the water vapor diurnal cycles of both δ 18 O v and d-excess v as also observed by Steen-Larsen et al (2013).…”
Section: Possible Causes For Change In Snow Surface and Water Vapor Imentioning
confidence: 82%
See 3 more Smart Citations
“…We therefore do not expect the snow surface to take up a significant isotopic signal from the surface hoar formed during the night. We do notice that, during clear-sky days, the diurnal cycle of sublimation/condensation is reflected in the water vapor diurnal cycles of both δ 18 O v and d-excess v as also observed by Steen-Larsen et al (2013).…”
Section: Possible Causes For Change In Snow Surface and Water Vapor Imentioning
confidence: 82%
“…We do not expect that the data gaps due to drift calibrations produce any significant effect on the analysis. When the vertical gradients of water stable isotopes were investigated in Steen-Larsen et al (2013), it was shown that they only depict diurnal gradients, and that water vapor isotopes covary at the day-to-day scale at different heights. This was also verified for our new measurements (not shown), and here we will only describe and discuss the measurements obtained at 3 m height ( Table 1).…”
Section: Crds-analyzer Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas cryogenic trapping provides grab samples generally averaging a couple of hours, laser spectrometry performs continuous high frequency (up to ∼ 1 Hz) measurements of δ v (Kerstel and Gianfrani, 2008). This technology offers new insights into processes that affect the isotopic composition of atmospheric water vapour and the number of studies based on continuous ground level isotope measurements over multiweek periods is continuously increasing, either using a tunable diode laser (TDL) (Lee et al, 2006;Wen et al, 2010Wen et al, , 2012Griffis et al, 2011;Welp et al, 2012), off-axis integrated cavity output spectroscopy (OA-ICOS) (Sturm and Knohl, 2010;Sunmonu et al, 2012;Farlin et al, 2013;SteenLarsen et al, 2013) or wavelength-scanned cavity ring-down spectroscopy (WS-CRDS) Tremoy et al, 2012;Steen-Larsen et al, 2013. Among these experiments are some low latitude studies which have focused on the tracing of tropical or subtropical convective activity in West Africa (Tremoy et al, 2012) or in South America .…”
Section: Introductionmentioning
confidence: 99%